Modern Interpretation of the Role of Hormone Therapy in Prostate Cancer - Abdukadirovich, Rakmanov Xamza (Journal of Science in Medicine and Life, 2024)
According to the World Health Organization (WHO), the incidence of prostate cancer is constantly increasing all over the world, and it is the third most common cancer in our country, after malignant tumors of the lung and stomach. Up to 40% of men between 60 and 70 years of age and 70% of men over 80 years of age have various stages of prostate cancer [1, 4]. Due to the specific characteristics of the clinical course, the prostate tumor may not only not affect the patient's well-being for many years, but also may not manifest itself in any way. The results of modern studies have shown that none of the currently used non-invasive methods can provide one hundred percent information about the presence of prostate cancer [2, 3]. In this regard, in order to improve the diagnosis and detection of oncological process in the prostate gland in the early stages, the revolutionary HistoScan device was created and is being successfully used [5]. It is a patented technology for differentiation, characterization and imaging of prostate tissue based on ultrasound backscatter analysis. This device can perform an ultrasound examination of the prostate gland with a high degree of accuracy, identify areas of suspicious tissue for cancer. Thus, the histoscan makes it possible to suspect prostate cancer (T 1 - T 2 stages). By displaying this information in the form of a 3D model and a map of the prostate, it is possible to determine the location and size of tumor tissue, to obtain targeted tissue samples during biopsy, to reduce the number of tissue columns of biopsy material, as well as to reduce the non-radical condition. allows observation. cancer therapies, and furthermore, we consider the possibility of targeting using histoscan mapping during focal therapy for prostate cancer.